Pengaruh Model Project Based Learning Berbasis Daur Ulang Sampah terhadap Keterampilan Berpikir Kreatif Siswa - Hilia Rahmadina; Siti Nurhidayati; Baiq Muli Harisanti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Creative thinking skills are essential in science education; however, teacher-centered instruction often limits students' opportunities to generate diverse alternative solutions. This study aimed to analyze the impact of a waste-recycling-based Project-Based Learning (PjBL) model on the creative thinking skills of 7th-grade students regarding the topic of interactions between living organisms and their environment. A quasi-experimental method with a non-equivalent control group design was employed. The sample consisted of 62 students, divided into an experimental group (31 students) and a control group (31 students). Data were collected through creative thinking skills tests, observations of lesson implementation, project assessments, and documentation, and subsequently analyzed using N-Gain and Mann-Whitney U tests. The results showed that the average pre-test and post-test scores for the experimental group rose from 39.32 to 67.45, while the control group increased from 41.45 to 54.16. The Mann-Whitney U test revealed a significant difference between the two groups (p < 0.001). The experimental group's N-Gain score was 0.46 (moderate category), which was higher than the control group's score of 0.22 (low category). Thus, the waste-recycling-based PjBL model has a significant impact and fosters greater improvement in students' creative thinking skills. This model offers a viable alternative for science instruction by integrating creativity, problem-solving, and environmental awareness.